PRODUCTION OF XYLOSE REDUCTASE AND XYLITOL BY Candida guilliermondii USING WHEAT STRAW HYDROLYSATES - & et al., Kklaif (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The objective of this study is to evaluate the production of Xylose reductase (XR) and Xylitol by Candida guilliermondii using wheat straw hydrolysates (WSH) supplemented with 2.0 g/l of (NH4)2SO4 and 0.1 g/l of CaCl2.2H2O as fermentation media . Wheat straw hydrolysis run at 121°C for 15 min. by diluted sulfuric acid . The fermentation process was conducted on a shaker bath (150 rpm) at 30C for 20 h in three separate flasks using different concentration of Xylose being , 30% Xylose , WSH(27.13 g/l Xylose)and WSH plus 30 g/l Xylose. The best concentration( WSH plus 30 g/l Xylose ) was chosen to run the fermentation process for XR production at different incubation temperature ( 20, 25, 30, 35, 40, 45 C, different pH values (5, 5.5, 6, 6.5 and 7) and different fermentation period (5 , 10 , 15,20 ,25 ,30 h ). The results indicated that the optimum condition for XR production was using 30%Xylose plus WSH at pH 6 over 20h incubation at 30 C. The crude extract of Xylose reductase was used to reduce Xylose into Xylitol with simultaneous oxidation of NADPH. The crude extract of XR was able to convert about 90 % 0f the Xylose to Xylitol through 24 h. incubation at 30°C.According to these findings WSH can be used as a promising source for Xylose to produce Xylose reductase enzyme by Candida guilliermondii and the crude extract could be used successfully in conversion of Xylose to Xylitol.